Evaluation of prescription pattern of antimicrobials in the treatment of respiratory tract infections in pediatric patients attending a tertiary care hospital - Patel, Tejal C.; Sapra, Simran A.; Bhave, Kiran A.; Pandit, Prasad R.; Mauskar, Anupama V.; Singh, Mohit Kumar (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Irrational use of antimicrobials is a complex and multifactorial problem in developing countries. Prescriptions not adhering to the treatment guidelines, self-medication, inappropriate use of drugs by patients can inadvertently lead to development of antimicrobial resistance. An observational study was designed to evaluate antimicrobial use in pediatric population with respiratory tract infections and its adherence to national treatment guidelines. Methods: This was a cross sectional observational study initiated after taking institutional ethics committee permission. The prescriptions of children diagnosed with upper respiratory tract infections and lower respiratory tract infections (LRTI) were screened. Their demographic profile and details of drugs prescribed were recorded. Results: Out of 230 pediatric prescriptions,155 (67%) were from outpatient department and 75 (33%) from those admitted in ward. Total 145 children were diagnosed with URTI whereas 85 had LRTI. In this study, 60 children with URTI received combination of amoxicillin and clavulanic acid (Co-amoxiclav) whereas 66 children with LRTI received Co-amoxiclav,18 ceftriaxone (N=18), 6 vancomycin (N=6) and 18 were prescribed oseltamivir (N=18), either alone or in combination. Other drugs prescribed included, paracetamol for fever and cough syrups. Out of 195 drugs prescribed by brand names, 138 (70.8%) were antimicrobials. Fixed dose combination amoxicillin and clavulanic acid, paracetamol and cough syrups were available from hospital pharmacy. None of the prescriptions had polypharmacy. Conclusions: URTI was treated using single antimicrobial whereas LRTI was treated with more than one antimicrobials or combination of antimicrobial and antiviral agent. The prescriptions were in accordance with the national treatment guidelines.